MicroRNAs in cancers and neurodegenerative disorders - Saito, Yoshimasa; Saito, Hidetsugu (Frontiers in Genetics, 2012)
MicroRNAs (miRNAs) are small non-coding RNAs which function as endogenous silencers of various target genes. MiRNAs are expressed in a tissue-specific manner and playing important roles in cell proliferation, apoptosis, and differentiation during mammalian development. Links between miRNAs and the initiation and progression of human diseases including cancer are becoming increasingly apparent. Recent studies have revealed that some miRNAs such as miR-9, miR-29 family and miR-34 family are differentially expressed in Alzheimer’s disease, Parkinson’s disease and Huntington’s disease. These miRNAs are also reported to act as tumor suppressors during human carcinogenesis. In this review, we discuss about miRNAs which are important in the molecular pathogenesis of both cancer and neurodegeneration. Cancer and neurodegenerative disorder may be influenced by common miRNA pathways that regulate differentiation, proliferation and death of cells.